EXPLORATION OF SELF MANAGEMENT OF HYPERTENSION PATIENTS IN THE CITY OF JAYAPURA - Fitriani; Titi Iswanti Afelya (Journal of Islamic Nursing, 2023)
Abstract Introductions : Hypertension is an asymptomatic chronic disease that can lead to complications and death. To control hypertension, patients can do pharmacological or non-pharmacological treatment. In non-pharmacological treatment, patients can make lifestyle changes in daily behavior, so that patients are responsible for themselves, which is called self management. The application of self management can reduce the risk of complications in patients. Aims : This study aims to identify Self Management in patients with hypertension. Methode : The research method is an analytic survey with a cross sectional study design. Identification of self management of hypertension patients using the Hypertension Self Management Behavior Questionaire (HSMBQ). The research sample was hypertension patients at Jayapura City Hospital selected by simple random sampling. The results of this study indicate that self management of hypertension patients is in the good category. Good self management can help patients manage their disease and improve their quality of life. Keywords: Hypertension, Self Management.